2017
DOI: 10.18203/2394-6040.ijcmph20171331
|View full text |Cite
|
Sign up to set email alerts
|

Study to assess predictive value of waist to height ratio and body mass index as a risk factor of hypertension and type 2 diabetes mellitus

Abstract: Background: Hypertension and diabetes have become important world-wide public-health challenges. Assessment of risk for Hypertension and Diabetes requires identifying an easy tool that can be used by health workers in screening programmes. To compare predictive value of WHtR against BMI in assessing risk of Hypertension and Diabetes. Methods: A case-control study was carried out at MB Hospital and Urban Health Training Centre (UHTC) attached to RNT Medical College, Udaipur, Rajasthan. Selected individuals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…This difference may be the probable cause of the association of SH with WHtR. In ROC, an AUC for WHtR was 0.592 and for BMI was 0.514, which concluded that WHtR could be a better indicator for diagnosing hypertension than BMI among the study population in the present study, which could be substantiated with results of previous studies [28][29][30].…”
Section: Discussionsupporting
confidence: 88%
“…This difference may be the probable cause of the association of SH with WHtR. In ROC, an AUC for WHtR was 0.592 and for BMI was 0.514, which concluded that WHtR could be a better indicator for diagnosing hypertension than BMI among the study population in the present study, which could be substantiated with results of previous studies [28][29][30].…”
Section: Discussionsupporting
confidence: 88%
“…Figures generated indicated that all mean anthropometric measures were towards higher sides both in men and women. Evidences reported the association of extended anthropometry measurements with hypertension [20,21], cardiovascular risk and metabolic syndromes [22][23][24], heart failure [25,26] and diabetes [26,27]. A WHO expert consultation [14] reviewed scientific evidence that suggested Asian populations have different associations between BMI, percentage of body fat, and health risks than do European populations.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%